Allelopathic Effects of Native Versus Invasive Plants on One Major Invader - Thiébaut, Gabrielle; Tarayre, Michèle; Rodríguez-Pérez, Héctor (Frontiers in Plant Science, 2019)
Allelopathy is defined as the effects (stimulatory and inhibitory) of a plant on the development of neighboring plants through the release of secondary compounds. Autoallelophaty is the beneficial or harmful effect of a plant species on itself. The allelopathic potential belonging to a native species could induce a biotic resistance against invasive plants, whereas allelochemicals released by exotic species could favor the establishment of invasive species (invasional meltdown). The aim of our study was to examine the potential allelopathic effect of four plant species on the target species Ludwigia hexapetala using two experiments. In the first experiment, we tested the allelopathic effect of root and leaf leachates of the two congeneric exotic species Ludwigia hexapetala and Ludwigia peploides on L. hexapetala, while in the second experiment, we studied the allelopathic effect of root and leaf leachates of a sympatric exotic species Myriophyllum aquaticum and of one native species Mentha aquatica on L. hexapetala. We measured the stem length to calculate the relative growth rate and four physiological traits (nitrogen balance index and flavonol, chorophyll, anthocyanin indices) of the target plants on a weekly basis. At the end of the experiment, we determined the aboveground and belowground biomass. We also counted the number of lateral branches and measured their lengths. We found that the root leachates of L. peploides and of Myriophyllum aquaticum had stimulated the synthesis of flavonols of L. hexapetala. Leaf leachate of L. hexapetala also stimulated its own flavonol synthesis. Also, the root leachate of L. peploides had stimulated the total biomass and length of lateral branches of L. hexapetala, whereas the production of lateral branches had been stimulated by root leachates of both Ludwigia species and by leaf leachate of Myriophyllum aquaticum. The autoallelopathy of L. hexapetala could explain its invasiveness. Both leachates produced by Mentha aquatica had no effect on the physiological and morphological traits of the invasive L. hexapetala and indicated no biotic resistance in the recipient community. The two invasive plant species Myriophyllum aquaticum and L. peploides could favor the establishment of L. hexapetala. These results suggested an “invasional meltdown.”